PENERAPAN TEKNOLOGI PEMBUATAN PUPUK CAIR RAMAH LINGKUNGAN DARI LIMBAH KULIT PISANG DAN NANAS MENGGUNAKAN AKTIVATOR EM4 - Kunda, Rony Marsyal; Kakisina, Pieter; Salamor, Reinhard; Manuhutu, Fredrik; Lakoan, Milda Rianty (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2025)
Household organic waste such as banana and pineapple peels are often not optimally utilized, even though they contain nutrients that are good for plants. This community service activity aims to provide counseling and training on making environmentally friendly liquid fertilizer by utilizing banana and pineapple peel waste using EM4 activator to the community in Kamal Village, West Seram Regency (SBB), Maluku Province. Through a participatory approach, this activity involves the community directly in the process of making liquid fertilizer, starting from the preparation of ingredients, fermentation, to application to plants through foliar spraying and direct watering to the planting media with a measured dose (50-100 ml of liquid fertilizer / 1 liter of water) every 7 days. This activity was carried out in 2 stages including the extension and training stages, as well as the monitoring and evaluation stages. The results of the activity showed an increase in participants' knowledge and skills in managing organic waste into useful and environmentally friendly products. With this activity, it is hoped that the community can apply this simple technology independently to support sustainable agriculture and reduce environmental pollution